Evaluación de la Adición de Yema de Huevo y Crema de Leche al diluyente, para la Crioconservación del Semen Canino. - Proaño Montesdeoca, Paola Estefanía (2019)
In the actuality the cryoconservation of canine semen, is a technique that is in full bloom, and there is not a cryoconsevative exclusive for canines, having in a higher percentage of lost in the seminal quality through the process of cryoconservation, causing a decrease of the motility and the vitality and an increase the sperm mortality. It the objetive of this work is to evaluate the addition of egg yolk and milk cream to the diluent, for cryoconservation of canine semen. In the biotechnology laboratory of the reproduction of Universidad Técnica de Cotopaxi. 3 canine dogs were selected randomly, from different races with ages ranging from 2 to 6 years and normal health conditions. It was extracted through a technique of manual collection, the seminal sample was evaluated by the helping of the Neubauer camera and the microscope, macroscopic characteristics were analized as volume, color, smell and pH and microscopic characteristics as concentration, motility and mortality of canine ejaculated in pre-freezing and post-thawing making values using specific data with the use of egg yolk and cream of milk for the biological substrate efected, during the first step of the procedure, initial values were obtained from each of the parameters, these being the comparison pattern to be used with the obtained data during the rest of the experiment, these were analyzed and processed with helping of the Excel program. For every one of the evaluated parameters were found there is percentage values differences between the use of egg yolk as cryoconservate getting obtaining optimal results in the seminal quality both in the pre-freezing and post-thaw, while that with the addition milk cream, low results were obtained in the seminal quality. With these results it is verified that when is used the seminal sample with yolk of egg it produces better results regarding the cryoconservation at the use of the cream of milk, positioning this material as a good cryoconservative of the canine semen.